Lumbar puncture in children with acute lyhmphoblastic leukaemia / Noor Hidayah Saarey@Ghazali - Noor Hidayah, Saarey@Ghazali (2017)
Title : Lumbar puncture in children with acute lymphoblastic leukaemia. Introduction : Acute lymphoblastic leukaemia (ALL) is the most common malignancy diagnosed in children, representing more than a quarter of all paed iatric cancers. Lumbar puncture (LP) is a diagnostic and therapeutic clinical procedure in paediatric oncology. Diagnostically, LP is routinely performed to detect the existence of cancer cells in the cerebrospinal fluid (CSF) whilst therapeutically, lumbar puncture is performed to deliver intrathecal chemotherapy. For the past 6 years, Ma-Spore ALL 2010 protocol have been used in University Malaya Medical Centre (UMMC), for the treatment of paediatric acute lymphoblast leukaemia (ALL) based-on patient risk stratification, which involved diagnostic and multiple therapeutic LP. The aim of this study is to identify the prevalence or performing successful LP in single attempt, risk factors associated with it, to describe the complications related to lumbar puncture and sedation used. This study also aim to identify the prevalence of parental reluctance in giving consent for their children first LP and whether they needed re-consenting/re-explanation for subsequent LPs, as well as to identify the relationship between parental reluctance and need for reconsenting and their psychosocial background. Another aim of this study is to validate a previous formula used for an ideal depth of needle insertion for a successful LP (Chong, 2009).